Ligand dechelation effect on a [Co(tpy)2]2+ scaffold towards electro-catalytic proton and water reduction. (12th February 2019) - Majee, Karunamay; Padhi, Sumanta Kumar
Abstract : This study presents the synthesis of the 4-(2, 6-di(pyridin-2-yl)pyridin-4-yl)quinoline (4Ql-tpy) ligand and H2 evolution by corresponding cobalt complex, i.e. [Co(4Ql-tpy)2 ]Cl2 . Abstract : This study presents the synthesis of the 4-(2, 6-di(pyridin-2-yl)pyridin-4-yl)quinoline (4Ql-tpy) ligand and its corresponding cobalt complexes, i.e. [Co(4Ql-tpy)2 ]Cl2 and [Co(4Ql-tpy)2 ](PF6 )3 . The [Co(4Ql-tpy)2 ]Cl2 complex has been employed for electro-catalytic reduction of protons in DMF/H2 O (95 : 5 v/v) as well as in phosphate buffer (pH 4.0–7.0). The spectroscopic investigations reveal the dissociation of one of the 4Ql-tpy ligands from the [Co(4Ql-tpy)2 ]Cl2 complex in the presence of excess AcOH in organic medium. However, in phosphate buffer it is evident that the dechelation of one of the peripheral pyridine rings followed by the protonation of pyridine-N occurs with the subsequent coordination of one water molecule. The aqueous electrochemical studies reveal that the Co(i ) species is dependent on the proton concentration and the gradient for potential vs. pH indicates that a PCET (1H + /1e − ) is involved between [Co II (4Ql-tpy)( 2 4Ql-tpy)(OH2 )] 2+ and [Co I (4Ql-tpy)( 2 4Ql-tpyH)(OH2 )] 2+ in the pH range 2.8 to 8.0. The plausible mechanism has been described based on the spectroscopic and electrochemical investigations.